Rivalry, Ritual, and Residues: Tracking Environmental Damage in Indonesian Football Culture - Anshari, Faridhian (International Journal of Environmental Communication (ENVICOMM), 2025)
This study investigates the cultural dynamics of Indonesian football supporters by focusing on rivalry, ritual, and the residues produced through visual swearing in urban spaces. Tracking local derbies and inter-group tensions, the research employs theories of collective behaviour alongside the neuro-psycho-social framework to explain how swearing operates as a ritualised emotional mechanism that regulates tension, reinforces solidarity, and asserts territorial boundaries among rival groups. Conducted through one-year qualitative ethnography, the study draws on participant observation, brief interviews, and document analysis of supporter posters, stickers, and graffiti. The findings reveal a critical spatial shift. Inside stadiums, swearing takes on ritual value: it amplifies rivalry, intensifies match-day atmosphere, and channels collective emotions in controlled ways. Outside stadiums, however, these ritual expressions leave material residues, most visibly through posters and stickers affixed to walls, trees, and road signs, as well as rivalry-driven graffiti. These visual forms of swearing extend symbolic aggression into public environments and generate long-lasting environmental damage. By connecting collective emotional behaviour with ecological consequences, this study introduces an analytical perspective rarely addressed in scholarship on swearing, which often focuses on individual or interpersonal dimensions. The findings offer strategic insights for supporter groups, football authorities, and urban policymakers seeking to preserve rivalry culture while reducing its environmental impact. Ultimately, the research argues that supporter expression must be understood not only as cultural ritual but also as a practice with measurable environmental residues.